2016
DOI: 10.1016/j.ijsu.2015.12.007
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of staple line reinforcement during laparoscopic sleeve gastrectomy: A meta-analysis of randomized controlled trials

Abstract: Staple line reinforcement using buttressing or roofing materials could reduce staple line hemorrhage and overall complications. No obvious advantages of oversewing the staple line were found and it took longer operative time. No significant reduction in leak rate was evidenced after reinforcement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(30 citation statements)
references
References 24 publications
2
28
0
Order By: Relevance
“…The results of our study advise against a distance to the pylorus <5 cm from the first stapling as it is associated with increased mortality; however, other authors recommend starting the section close to the pylorus to achieve greater weight loss [36]. In our study, the use of bioabsorbable polyglycolic acid reinforcement materials proved to be a protective factor for bleeding but had no impact on fistulas; similarly, other studies have shown a reduction in bleeding [37,38], but the reduction in fistulas is subject to controversy [39][40][41]35]. As for RF for mortality, anticoagulant treatment, DM2, smoking, and the distance to the pylorus from the first stapling <5 cm were independent factors; however, the variables that had the most influence on mortality were fistula and pulmonary thromboembolism.…”
Section: Discussionmentioning
confidence: 45%
“…The results of our study advise against a distance to the pylorus <5 cm from the first stapling as it is associated with increased mortality; however, other authors recommend starting the section close to the pylorus to achieve greater weight loss [36]. In our study, the use of bioabsorbable polyglycolic acid reinforcement materials proved to be a protective factor for bleeding but had no impact on fistulas; similarly, other studies have shown a reduction in bleeding [37,38], but the reduction in fistulas is subject to controversy [39][40][41]35]. As for RF for mortality, anticoagulant treatment, DM2, smoking, and the distance to the pylorus from the first stapling <5 cm were independent factors; however, the variables that had the most influence on mortality were fistula and pulmonary thromboembolism.…”
Section: Discussionmentioning
confidence: 45%
“…A meta-analysis of RCTs and a proportion meta-analysis addressed the topic of staple line reinforcement [94,95]. Staple line reinforcement was associated with a 30% lower risk for complications overall (RR 0.7, 95% CI 0.5 to 0.9) and this finding was associated with high certainty.…”
Section: Justificationmentioning
confidence: 99%
“…These results were reported in multiple randomized controlled trials which demonstrated that the staple-line reinforcement in LSG had benefits over the postoperative staple-line hemorrhage and leakage. [17][18][19][20][21] Aggrwal et al and Sroka et al suggested that the diminished bleeding rate after oversewed LSG may be attributed to the learning curve effect and not only the efficacy of oversewing. 18,20 Miller et al and Kasalicky et al stated that the low hemorrhage rate with the buttressing material usage could be related to the more compression during tissue excision.…”
Section: Discussionmentioning
confidence: 99%